'But I want to say "I means love you"'. (9th December 2021) - Nguyen, Hanh thi; Nguyen, Minh Thi Thuy
Abstract : Family talk is a rich site for children's language learning as well as navigating into cultural values, social roles and stances. This study examines a child's stancetaking in language-focused interaction initiated by the parent, in order to understand children's role in language learning as a social activity and in their own language socialization. Conversation analysis of audio-recorded child–parent conversations in family settings over eight months reveals the varied epistemic and affective stances that the child displayed towards language forms, cultural norms, the parents' stances, and the language-focused activity itself. We show that the child changed over time to orient to a correctness norm as part of his socialization into the family's beliefs and values regarding language. We argue that talk about language forms is deeply connected with participants' stances towards language and cultural norms as well as toward others' stances and actions, and that for a sound understanding of language learning as a social activity, detailed examinations of children's and caregivers' stancetaking in interaction are indispensable.